Efficacy of Tumor-Infiltrating Lymphocytes Combined with IFN-α in Chinese Resected Stage III Malignant Melanoma - Wei Li; Linping Xu; Yaomei Wang; Lingdi Zhao; Daniel B. Kellner; Quanli Gao (Journal of Immunology Research)
Background. This study aims to explore the efficacy of tumor-infiltrating lymphocytes (TIL) along with interferon-α (IFN-α) to treat stage III malignant melanoma (MM) patients in China. Methods. Between May 2010 and October 2014, 77 patients of stage III MM who underwent surgery were collected in this study. These patients were divided into two groups: patients who received TIL + IFN-α ± RetroNectin-activated cytokine-induced killer cells (R-CIK) in Arm 1 (n=27) and IFN-α ± R-CIK in Arm 2 (n=50) as adjuvant therapy. The primary endpoints were disease-free survival (DFS) time and DFS rates measured at time points of 1, 2, and 3 years. The secondary endpoints were overall survival (OS) rates measured at time points of 1, 2, 3, and 5 years as well as OS as evaluated by Kaplan-Meier. Results. Our results indicated that the median DFS and OS in Arm 1 were significantly better than those in Arm 2. The data also demonstrated that DFS rate and OS rates in Arm 1 were significantly better than those in Arm 2 at all measured time points. Conclusion. Patients who undergo surgical excision of stage III MM appear to enjoy prolonged DFS and OS when treated with TIL + IFN-α compared to IFN-α alone.